7-Methyl-5-[(4-methylbenzene)sulfonyl]-2H,5H-[1,3]dioxolo[4,5-f]indole: crystal structure and Hirshfeld analysis - Ali, Akbar; Zukerman-Schpector, Julio; Weber Paixão, Márcio; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2018)
In the title indole derivative, C17H15NO4S, the fused dioxolo-indole system is essentially planar [r.m.s. deviation of the 12 ﬁtted atoms = 0.0249 A ˚ ] and is effectively perpendicular to the appended 4-tolyl ring, forming a dihedral angle of 89.95 (6). Overall, the molecule has the shape of the letter L. In the crystal, supramolecular layers in the ab plane are formed via weak 4-tolyl-C—H....(C6ring of indole) and S—O.... 1,3-dioxole) contacts. The aforementioned interactions along with interatomic H...H and H...O contacts are all shown to make signiﬁcant contributions to the calculated Hirshfeld surfaces.